2018
DOI: 10.3389/fcell.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Spiral Ganglion Non-neuronal Cells into Neurons: Toward Ameliorating Sensorineural Hearing Loss by Gene Therapy

Abstract: Primary auditory neurons (PANs) play a critical role in hearing by transmitting sound information from the inner ear to the brain. Their progressive degeneration is associated with excessive noise, disease and aging. The loss of PANs leads to permanent hearing impairment since they are incapable of regenerating. Spiral ganglion non-neuronal cells (SGNNCs), comprised mainly of glia, are resident within the modiolus and continue to survive after PAN loss. These attributes make SGNNCs an excellent target for repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 88 publications
2
42
0
Order By: Relevance
“…Previous studies showed that cochlear glia cells were plastic and could be converted into SGNs in vitro. 15 Our current study further demonstrated plasticity of neonatal glial cells in vivo. Our data supported that neonatal glial cells distributed in middle and apical cochlear turns were more plastic than those in basal turn (data not shown).…”
Section: Cochlear Neonatal Glia Cells Are Plastic and Can Be Reprogsupporting
confidence: 71%
See 3 more Smart Citations
“…Previous studies showed that cochlear glia cells were plastic and could be converted into SGNs in vitro. 15 Our current study further demonstrated plasticity of neonatal glial cells in vivo. Our data supported that neonatal glial cells distributed in middle and apical cochlear turns were more plastic than those in basal turn (data not shown).…”
Section: Cochlear Neonatal Glia Cells Are Plastic and Can Be Reprogsupporting
confidence: 71%
“…Neurog1 (also known as Ngn1 ) and Neurod1 are b‐HLH transcription factors that are necessary for SGN development . In addition, Neurod1 is known to reprogram chromatin, induce neuronal gene expression, and is sufficient to successfully reprogram in vitro cochlear glial cells into SGNs which express neuronal markers, Tuj1, Map2, and Prox1 . We set out to induce ectopic Ngn1 and Neurod1 expression in neonatal cochlear glial cells in vivo via the Cre/Loxp‐mediated genetic approach …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CORO2B, a central nervous system gene, is involved in brain cellular cytoskeleton rearrangement and motility and molecular trafficking [34,35]. The up-regulated expression of CORO2B has been detected in induced neurons [36]. It is pointed out that CORO2B is associated with the neurological disease such as neuroblastoma [37].…”
Section: Discussionmentioning
confidence: 99%